Low-Complexity Receiver Using Undersampling for Guard-Band SSB-DDO-OFDM - Ming Chen; Qinghui Chen; Hui Zhou; Zhiwei Zheng; Jing He; Lin Chen (IEEE Photonics Journal)
A guard-band-based and single-side-band (SSB) modulation scheme is usually employed to improve receiver sensitivity and avoid power fading for the direct-detection optical orthogonal frequency-division multiplexing (DDO-OFDM). In this paper, we take advantages of analog-to-digital converter (ADC) undersampling to achieve a low-complexity receiver for guard-band SSB-DDO-OFDM. By using an electrical bandpass filter, the signal-to-signal beating interference is removed from the guard-band, and the desired OFDM signal is sampled at a rate twice its signal bandwidth rather than its highest frequency component. The guard-band will be filled with the aliased components which can be used to fully recover the transmitted data, and the discrete Fourier transform size at the receiver side is reduced by more than half. As a result, the implementation complexity of the receiver can be greatly reduced with the lower ADC sampling rate and reduced digital signal processing complexity. The feasibility of the proposed low-complexity receiver is investigated by numerical simulations. When the quantization noise is not dominant, the simulations show that the proposed low-complexity guard-band SSB-DDO-OFDM has similar error vector magnitude performances with the conventional one over different bias voltages and single-mode fiber links.